The Role of CA and Associated Technologies in Achieving the SLOs - Concept Note - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2012)
This strategic study will examine the evidence base for conservation agriculture and associated soil-based technologies in achieving the system-level outcomes of the new CGIAR system. The concept note describes the motivation for the study, its objectives, and outlines a workplan.